Comparative Studies on Flour Proximate Compositions and Functional Properties of Selected Pakistani Rice Varieties: Comparative Studies on Flour Proximate Compositions and Functional Properties - Jamal, Suraiya; Qazi, Ihsan Mabood; Ahmed, Ishfaq (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
The aim of this study was to evaluate the proximate and functional properties of flours obtained from various rice varieties, i.e., Super Basmati Shaheen, Super Basmati Kainat, Super Fine, JP5, Basmati 385, Fakhr-e-Malakand grown in different areas of Pakistan. Moisture content, ash content, crude protein, crude fat, water absorption index, water solubility and swelling power varied significantly (P<0.05) from each other. Moisture content, ash content, crude protein and crude fat of rice flour ranged from 5.46–7.08%, 0.48–1.23%, 8.02–9.85% and 0.43–1.5%, respectively. While, functional properties such as water absorption index, water solubility index and swelling power were found in the range of 5.38–6.26 (g/g), 1.95–4.94% and 5.74–7.64 (g/g), respectively. The results showed that the functional properties of rice flour were greatly influenced by the compositional variations of various rice varieties.